Implementasi Kurikulum Merdeka Pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan di Sekolah Penggerak SMP Se-Kabupaten Hulu Sungai Tengah - Hidayat, Muhammad Firdaus; Yuwono, Cahyo; Raharjo, Hermawan Pamot (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the implementation of the independent curriculum in Physical Education, Sports, and Health subjects in Middle School Driving Schools throughout Hulu Sungai Tengah Regency. This research uses a descriptive qualitative approach. This research uses a qualitative descriptive method by collecting data through observation, interviews, and documentation, then analyzing through several stages, namely reduction, display, and conclusion drawing/verification, and checking the validity of the data using triangulation, namely triangulation of sources and techniques. The results of research carried out at SMP Mobilization Schools in Hulu Sungai Tengah Regency are: in planning learning, by starting with carrying out diagnostic assessments regarding students' readiness, interests, and profiles to carry out mapping, determining essential material, preparing systematic learning implementation plans. The teaching tools used by teachers are appropriate and refer to the teaching tools provided by the Ministry of Education and Culture; learning carried out by teachers tries to refer to the principles of learning in the independent curriculum and is at a developing stage with the consideration that the learning carried out is centered on students and the accuracy of differentiated learning methods, namely differentiation of content, process, product and environment; Evaluation is carried out by referring to the evaluation principles launched by the Ministry of Education and Culture, such as motivating, providing direction and enrichment. In conclusion, the implementation of the independent curriculum in middle school driving schools in Hulu Sungai Tengah district has been good, proven by the selection of essential materials by the Ministry of Education and Culture's guidelines, the implementation of learning by the stages planned by the teacher in the teaching module, evaluation of learning that has been good with its implementation. The stages include the evaluation of attitudes, knowledge with tests, and assessment of skills with practice. Keywords: Implementation; Independent Curriculum; Driving School; Sports Physical Education and health